DESAIN MATERI AJAR BERBASIS LOGIKA KOMPUTASI DALAM BENTUK BUKU SAKU - Elita Arcelina Sandi; Suyatno Suyatno; Titik Indarti; Moh Arif Susanto (PIONIR: JURNAL PENDIDIKAN, 2022)
Student logic is an approach that makes it easy and can be used by teachers to implement meaningful learning and train critical thinking skills in presenting the text of the observation report. With this computational logic-based pocket teaching material, the researcher hopes that learning to present the text of the observation report will be more effective and creative and innovative because the computational learning approach involves students and can increase critical and independent thinking in learning to obtain information and meaningful learning experiences. Expert test results obtained a score of 80%. The results of small-scale testing obtained a score of 90%. The conclusion obtained from this study is that the teaching material of the text of the observation report based on computational logic in the form of a pocket book to develop self-reliance in learning to appreciate is included in the appropriate category.